Differential gene expression of Asian citrus psyllids infected with ‘Ca. Liberibacter asiaticus’ reveals hyper-susceptibility to invasion by instar fourth-fifth and teneral adult stages - He, Ruifeng; Fisher, Tonja W.; Saha, Surya; Peiz-Stelinski, Kirsten; Willis, Mark A.; Gang, David R.; Brown, Judith K. (Frontiers in Plant Science, 2023)
The bacterial pathogen Candidatus Liberibacter asiaticus (CLas) is the causal agent of citrus greening disease. This unusual plant pathogenic bacterium also infects its psyllid host, the Asian citrus psyllid (ACP). To investigate gene expression profiles with a focus on genes involved in infection and circulation within the psyllid host of CLas, RNA-seq libraries were constructed from CLas-infected and CLas-free ACP representing the five different developmental stages, namely, nymphal instars 1-2, 3, and 4-5, and teneral and mature adults. The Gbp paired-end reads (296) representing the transcriptional landscape of ACP across all life stages and the official gene set (OGSv3) were annotated based on the chromosomal-length v3 reference genome and used for de novo transcript discovery resulting in 25,410 genes with 124,177 isoforms. Differential expression analysis across all ACP developmental stages revealed instar-specific responses to CLas infection, with greater overall responses by nymphal instars, compared to mature adults. More genes were over-or under-expressed in the 4-5th nymphal instars and young (teneral) adults than in instars 1-3, or mature adults, indicating that late immature instars and young maturing adults were highly responsive to CLas infection. Genes identified with potential for direct or indirect involvement in the ACP-CLas circulative, propagative transmission pathway were predominantly responsive during early invasion and infection processes and included canonical cytoskeletal remodeling and endo-exocytosis pathway genes. Genes with predicted functions in defense, development, and immunity exhibited the greatest responsiveness to CLas infection. These results shed new light on ACP-CLas interactions essential for pathogenesis of the psyllid host, some that share striking similarities with effector protein-animal host mechanisms reported for other culturable and/or fastidious bacterial- or viral- host pathosystems.